Gender Discrimination by Female Journalists Against Companies in the Media - Firda Aulia Miftahul Zanah; Suprihatin; E. Rizky Wulandari (LPPM Stikosa-AWS, 2023)
Reseacrh aims to find findings from the forms of discrimination experienced by female journalists by media companies in Surabaya. The research subjects consisted of four media in Surabaya, namely Suara Surabaya, Ngopibareng.id, Jawa Pos, and Jawa Pos Televisi. This study aims to determine the discrimination committed by editors in the media Suara Surabaya, Ngopibareng.id, Jawa Pos, and Jawa Pos Televisi (JTV) against their female journalists. In addition to knowing the perspective of the editor-in-chief on gender in the world of work and the media industry. Through explorative qualitative research methods, researchers seek data from various sources. The results of this study indicate that there are still many media in Surabaya that have not fully fulfilled the rights of female journalists. At the Jawa Pos Office there are lactation room facilities as well as a refrigerator to store breast milk (ASI). Meanwhile in Suara Surabaya, the communication pattern formed by the chief editor towards female journalists is different from that of male journalists. Other findings also concern the workload experienced by female journalists from Ngopibareng.id and Jawa Pos Televisi (JTV). Based on research showing that the media in Surabaya, only one that has a good perspective on gender, namely Jawa Pos. Meanwhile, the editors-in-chief of Suara Surabaya, Ngopibareng.id and Jawa Pos Televisi (JTV) still don't have a good perspective on gender.